Hospital food handlers in Niterói, RJ, Brazil: intestinal parasitism - Ana Eliza Port Lourenço; Claudia Maria Antunes Uchoa; Otilio Machado Pereira Bastos (Archivos Latinoamericanos de Nutrición)
A survey for intestinal parasites was carried out with food handlers from two private and three public hospitals in Niterói City, RJ, Brazil. The aim of this research was to verify the enteroparasites prevalence in this professional group. The investigation was divided in two phases. The first phase consisted of interviews with the participants; coproparasitological exams using Lutz, Faust et al. and Baermann techniques; under fingernail material analysis, using Mello et al. modified method; and educational lectures to food handlers. In the second phase, coproparasitological exams were repeated. Positive results were observed in 14.2% (17/120) and 17.1% (12/70) of the individuals in the first and second phases respectively. The most frequent parasite was Entamoeba coli, detected in 48.5% (16/33) of the samples with positive results. Under fingernail residues were observed in 19.2% (23/120) of the food handlers. E. coli cysts were found in one fingernail residue, likewise they were detected in the feces of the same food handler. Such data showed a potential transmission risk of intestinal parasites by food handling, indicating the need of adopting a diagnosis/orientation procedure as a bi-annual routine activity in hospitals, in order to improve the food service quality and population health condition.